Of bravery and invisibility : black lesbian activism in South Africa between 1980 and 2016 - Van der Westhuizen, Christi (University of Pretoria, 2018)
This study explores the experiences of Black lesbian activists in South Africa between 1980 and 2016. The study asks where does Black lesbian activism fit in the history of the broader struggle for political liberation, and in particular in the struggle for gay and lesbian rights, in South Africa. Secondly it asks whether there has been any change in how the intersecting challenges of race, class and gender have impacted this group of women. Thirdly, it asks what is the future of this type of activism. Participants revealed that the similar issues that plagued the gay and lesbian movement in the early 1980s still beset the movement postapartheid. Newer issues concern a lack of opportunity for new voices in the movement, a lack of skills development, and a narrow understanding of the issues that affect Black lesbians. The legal victories won for gay and lesbian people in the early years of democracy remain inaccessible to some Black lesbians, because they are still vulnerable to various forms of violence and abuse. It is with these findings that the study argues that Black lesbian activism, as a unique form of activism with a particular agenda, existed during the 1980s in South Africa, however invisible and small in scale. Continued activism is necessary for the realization of the rights of marginalized Black lesbian women, however it needs to become more inclusive and dynamic. It must devise and commit to new and innovative strategies of organizing, not just on the frontlines, but across a range of sectors and spaces of influence.